2023
DOI: 10.3390/jmse11010060
|View full text |Cite
|
Sign up to set email alerts
|

Confidence of a k-Nearest Neighbors Python Algorithm for the 3D Visualization of Sedimentary Porous Media

Abstract: In a previous paper, the authors implemented a machine learning k-nearest neighbors (KNN) algorithm and Python libraries to create two 3D interactive models of the stratigraphic architecture of the Quaternary onshore Llobregat River Delta (NE Spain) for groundwater exploration purposes. The main limitation of this previous paper was its lack of routines for evaluating the confidence of the 3D models. Building from the previous paper, this paper refines the programming code and introduces an additional algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…KNN considers the similarity factor between new and available data to classify an object into predefined categories. KNN has been widely used in many fields such as industry [7][8][9], machine engineering [10], health [11][12][13], marketing [14], electrical engineering [15], security [16][17][18], manufacturing [19], energy [20][21][22], aerial [23], environment [24], geology [25,26], maritime [27,28], geographical information systems (GIS) [29], and transportation [30].…”
Section: A Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…KNN considers the similarity factor between new and available data to classify an object into predefined categories. KNN has been widely used in many fields such as industry [7][8][9], machine engineering [10], health [11][12][13], marketing [14], electrical engineering [15], security [16][17][18], manufacturing [19], energy [20][21][22], aerial [23], environment [24], geology [25,26], maritime [27,28], geographical information systems (GIS) [29], and transportation [30].…”
Section: A Review Of Related Literaturementioning
confidence: 99%
“…In the field of geology, the authors [25] reported that the KNN algorithm was utilized for a three-dimensional envision of the stratigraphic structure of porous media related to sedimentary formations. In a similar work in geology, Bullejos et al [26] implemented a technique for the evaluation of KNN prediction confidence in that the three-dimensional model for the stratigraphic structure of porous media is approved. The results of their KNN-based method contributed to improving the predictability of groundwater investigations.…”
Section: A Review Of Related Literaturementioning
confidence: 99%
“…To get a model of another location, the procedures presented here can be mimicked, but these must be adapted to the new data of the new location, and researchers must make their own choices of how the model should be. Python has been used by us to produce other geological models in the recent past, but with a different perspective and different kind of data, as is the case of the Llobregat River Delta (Barcelona, Spain) [28][29][30][31].…”
Section: Google Earth Promentioning
confidence: 99%
“…Our previous experience with Python libraries for 3D visualization, including geological data handling [28][29][30][31], has been very important to develop new applications for visualizing 3D structural and stratigraphic geological features. These new applications included Jupyter notebooks, describing the methodology, and a Python code operative version, which are downloadable from the GitHub repository (https://github.com/bullejos/ visualizing-an-imbricate-thrust-system accessed on 4 July 2023).…”
Section: Introductionmentioning
confidence: 99%